+0  
 
0
34
6
avatar

Let f(x)=2x-3 and let g(x) be a function such that g(f(x))=5-4x. Find g(4).

 Jul 31, 2023
edited by Guest  Jul 31, 2023
 #2
avatar+753 
+1

g(f(x)) = 5 - 4xsimplifies to g(2x - 3) = 5 - 4x. We are trying to find g(4), so we try to make 2x - 3 equal to 4. If 2x - 3 = 4, then we know that 2x = 7, or x = 3 1 / 2. Putting this into 5-4x, we can see that 5 - 4 * 3.5, or 5 - 14, or 9. Therefore, g(4) is equal to -9

 Jul 31, 2023
edited by history  Jul 31, 2023

5 Online Users

avatar
avatar